Functional expression and segmental localization of rat colonic K-adenosine triphosphatase. - Lee, J (1995)
A putative cDNA for the colonic K-ATPase has recently been cloned (Crowson, M.S., and G. E. Shull. 1992. J. Biol. Chem. 267:13740-13748). Considerable evidence exists that there are two K-ATPases and active K absorptive processes in the rat distal colon: one that is ouabain sensitive and the other ouabain insensitive. The present study used the baculovirus expression system to express K-ATPase activity in insect Spodoptera frugiperda (Sf 9) cells and a polyclonal antibody (M-1), developed against a fusion protein produced from the 327 nucleotide fragment from 5' coding region of the putative K-ATPase cDNA, to identify the specific localization of the K-ATPase protein. K-ATPase activity (28.7 +/- 1.2 nmol inorganic phosphate/mg protein min) was expressed in plasma membranes isolated from Sf 9 cells infected with baculovirus containing recombinant DNA with the putative K-ATPase cDNA. Km for K for the K-ATPase was 1.2 mM. The expressed K-ATPase activity was not inhibited by ouabain (1 mM); while the Ki for vanadate inhibition was 8.3 microM. Western blot analysis with the M-1 antibody identified a 100-kD protein in apical membranes prepared from distal, but not proximal, rat colon. Immunohistochemical studies with M-1 antibody localized K-ATPase only in the apical membrane of surface cells, while an mAb (c464.6) against Na,K-ATPase localized basolateral membranes of both surface and crypt cells of rat distal colon. In conclusion, the putative K-ATPase cDNA encodes an ouabain-insensitive K-ATPase that is present only in the apical membrane of surface cells of rat distal colon.